2019
DOI: 10.1371/journal.pone.0220040
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with moderate neonatal hyperthyrotropinemia

Abstract: Background Maternal iodine deficiency is related to high neonatal thyroid-stimulating hormone (TSH) values, with the threshold of 5 mIU/L recommended as an indicator of iodine nutrition status. The objective of this study was to analyse possible risk factors for increased TSH that could distort its validity as a marker of iodine status. The clinical relevance of this research question is that if the factors associated with iodine deficiency are known, iodine supplementation can be introduced in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(34 reference statements)
0
8
0
2
Order By: Relevance
“…Gender is a known factor influencing neonatal TSH level. The percentage of neonatal HTT is higher among male newborns, in contrast with the higher number of female newborns with CH in general (6,16,39,40).…”
Section: How Does the Reported Frequency Of Htt Vary Depending On The Mode Of Identification And What Other Factors Does It Depend On?mentioning
confidence: 68%
See 3 more Smart Citations
“…Gender is a known factor influencing neonatal TSH level. The percentage of neonatal HTT is higher among male newborns, in contrast with the higher number of female newborns with CH in general (6,16,39,40).…”
Section: How Does the Reported Frequency Of Htt Vary Depending On The Mode Of Identification And What Other Factors Does It Depend On?mentioning
confidence: 68%
“…The disparity in the reported prevalence may also be in part to population genetics and ethnicity. The risk of high neonatal isolated TSH has been previously shown to be dependent on maternal ethnicity (6). A cohort study conducted in Skopje, the capital of Macedonia, also reported ethnic differences in the incidence of high serum TSH levels in neonates (46).…”
Section: How Does the Reported Frequency Of Htt Vary Depending On The Mode Of Identification And What Other Factors Does It Depend On?mentioning
confidence: 94%
See 2 more Smart Citations
“…Consistent with our result, Gupta et al (30) demonstrated that male neonates had slightly higher amount of CBTSH than their female counterparts. Cortés-Castell et al (31) have reported the risk of high neonatal TSH without congenital hypothyroidism is higher in males. Although paralleled results have been extracted by other studies (13,32), several reports emphasized on no signi cant association of mean cord blood TSH and sex (1,24,25,33).…”
Section: Discussionmentioning
confidence: 97%